Análise neurofarmacológica e neuroquímica da expressão de memórias espaciais - Furini, Cristiane Regina Guerino (2012)
Memories are not stored in its final form immediately after the acquisition. They undergo a long stabilization process known as consolidation. Consolidated memories can become labile again after the retrieval and susceptible to the action of amnesic agents. Thus, to persist must go through the re-stabilization process called reconsolidation. Several evidences indicate that the hippocampus plays an important role in both consolidation and reconsolidation process of different memories. In this way, we decided investigate the participation of NMDA and GABA receptors of dorsal hippocampus CA1 region on the retrieval and reconsolidation of spatial memory. We used the Morris water maze task (MWM) to demonstrate that infusion of AP5 (5 μg/μl), the selective antagonist of the NMDA receptor, into the dorsal hippocampus CA1 region of rats is able to block temporarily the retrieval of spatial memory. However, when we administered different doses and different times after the reactivation session in the absence of reinforcement is not observed any effect on spatial memory reconsolidation. While agonists of the glycine site of NMDA receptors, D-SER (10 μg/μl), improves the consolidation and the reconsolidation of spatial memory. Furthermore, we found that infusion of the agonist of GABA, muscimol (0.1 μg/μl), temporarily prevents the memory retrieval of MWM. However, when the animals received infusion of muscimol before the reactivation session and the protein synthesis inhibitor, anisomycin (160 μg/μl), immediately after this session, spatial memory remains inhibited. Thus, we have demonstrated that inhibition of NMDA receptors prevents the retrieval but not the reconsolidation of the spatial memory and the NMDA agonist is capable of improving consolidation and reconsolidation of memory, while the GABA activation temporarily prevents retrieval and the impairment of memory is maintained through inhibition of protein synthesis.